2018
DOI: 10.1002/anie.201810511
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of Carbon Monoxide and tert‐Butyl Nitrile by Intramolecular Proton Transfer in a Bis(Phosphido) Thorium Complex

Abstract: We report intramolecular proton transfer reactions to functionalize carbon monoxide and tert‐butyl nitrile from a bis(phosphido) thorium complex. The reaction of (C5Me5)2Th[PH(Mes)]2, Mes=2,4,6‐Me3C6H2, with 1 atm of CO yields (C5Me5)2Th(κ2‐(O,O)‐OCH2PMes‐C(O)PMes), in which one CO molecule is inserted into each thorium–phosphorus bond. Concomitant transfer of two protons, formerly coordinated to phosphorus, are now bound to one of the carbon atoms from one of the inserted CO molecules. DFT calculations were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 87 publications
2
28
0
Order By: Relevance
“…In addition, the 1 H NMR spectrum showed the (C 5 Me 5 ) 1À resonance at À1.35 ppm, but another resonance integrating to 18 protons was detected at 10.3 ppm. A signal in the 31 P NMR spectrum at 518.0 ppm was located.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the 1 H NMR spectrum showed the (C 5 Me 5 ) 1À resonance at À1.35 ppm, but another resonance integrating to 18 protons was detected at 10.3 ppm. A signal in the 31 P NMR spectrum at 518.0 ppm was located.…”
Section: Resultsmentioning
confidence: 99%
“…24 These complexes impart a mismatch between the hard, electropositive Lewis acidic actinide centre, and the so Lewis basic nature of phosphorus, and have been shown to afford unpredictable and unusual chemistry. [25][26][27][28][29][30][31][32][33][34] We recently showed that the U(III) complex, (C 5 Me 5 ) 2 U(THF) [P(SiMe 3 )(Mes)] reacts with Me 3 SiN 3 to form the U(VI) bis(imido) complex, (C 5 Me 5 ) 2 U(]NSiMe 3 ) 2 . 35 In order to prevent the formation of the bis(imido) complex, here, we used the mixed phosphido-methyl complexes (C 5 Me 5 ) 2 U(CH 3 )[P(SiMe 3 )(R)], R ¼ C 6 H 5 (Ph), 1; 2,4,6-Me 3 C 6 H 2 (Mes), 2.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they are less inclined to form strong interactions with ligands bearing soft-donor atoms such as phosphorus. Therefore, the actinide-phosphido bond should, and has been demonstrated, be relatively reactive [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of P–H bonds is an essential step in hydrophosphination , and hydrodecoupling , reactions; however, the mechanisms by which metal complexes perform P–H activations are not fully understood. For example, in our work on the reactivity of actinide phosphido complexes, P–H bond activations via σ-bond metathesis are observed, but other mechanisms by which P–H activations occur are less straightforward. Generally, most of these metal-mediated activations involve mononuclear metal complexes, while multimetallic or cooperative examples are limited. , Acquiring further mechanistic insight into these bond activations is important to afford strategies for the functionalization of phosphines, , which are of interest for a wide array of applications. The reactivities of metal alkyl , and hydride complexes, especially with electropositive metals, help to facilitate these bond activations, and thus a number of examples of P–H bond activation are known with f elements, nearly all involving lanthanide complexes. ,, …”
Section: Introductionmentioning
confidence: 97%